Jesuit chronicles and probabilism: The knowledge of American nature through Bernabé CoboAbstract - Maranguello, Carla (2025)
Jesuit probabilism, which characterized part of the doctrinal sources used in the Peruvian viceroyalty since the 16th century, had an important role in the perception of the American world. In this context, the chronicles played a complementary role in knowledge regarding the cultural and natural world and constituted instructional material from a religious and moral point of view. We will focus on Bernabé Cobo´s chronicles [1653], who dedicated part of his life to the observation and description of American nature, distancing himself from other natural histories by questioning parameters imposed as universal, a situation that impacted the conceptions of the moral and religious order. Our objective is to show that this is due to his connection with probabilism, having intensified his closeness to said philosophy through his membership in the order of the Society of Jesus.